Edible flowers: beauty, health and nutrition (Research, Society and Development, 2020)
The market for edible flowers is expanding worldwide, due to the greater interest of the population in foods with therapeutic properties and the need to conquer the market with different and innovative products. Flowers can be used in decorating and preparing food and drinks, adding aroma, flavor and color. However, the chemical composition of flowers must be known before human consumption. The objective was to discuss the most consumed species, their bioactive components and information on the quality, preservation and consumption of flowers. A bibliographic survey from 1992 to 2018 was carried out on the research platforms of ScienceDirect, SciELO and Periódicos Capes, where 40 articles were selected to serve as a database. Studies on consumer perception of consumption of edible flowers and their preparation are limited. The content of bioactive compounds is changed by the method of preparation. Consumer preference is for unprocessed or minimally processed forms (such as dried rose petals). Edible flowers are an entrepreneurial opportunity, whether for production for consumption, preparation of new products or extraction of bioactives.